World Literature I Beginnings to 1650 - Getty, Laura; Kwon, Kyounghye (Open textbook library., 2015)
This peer-reviewedWorld Literature Ianthology includes introductory text and images before each series of readings. Sections of the text are divided bytimeperiod in three parts: the Ancient World, Middle Ages, and Renaissance, and then divided into chapters by location.